INTERNALISASI NILAI-NILAI KARAKTER RELIGIUS MELALUI PEMBIASAAN AKTIVITAS KEAGAMAAN - Riyan Maulana Bakir; Feriska Listrianti (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Abdurachman Saleh Situbondo, 2026)
Character education plays a vital role in shaping students with noble character and a sense of responsibility. A key element of character education is the internalization of religious values, which serves as the foundation for developing positive attitudes and behaviors. Religious values do not only pertain to ritual worship but also encompass discipline, honesty, responsibility, tolerance, and social concern. This study aims to describe the process of internalizing religious values through the habituation of religious activities at SMP Negeri Satap Gerokgak. This research employs a qualitative method with a descriptive approach. Data collection techniques were conducted through observation, interviews, and documentation. The research subjects included the principal, Religious Education teachers, religious activity supervisors, and students. This study focuses on the implementation and involvement of students in various religious activities carried out routinely and systematically. These religious activities are classified based on their schedule: daily, weekly, monthly, and annual activities. Daily religious activities include collective prayer before and after lessons, Dhuha prayer, and congregational Dhuhur prayer. Weekly, monthly, and annual activities include religious gatherings (pengajian), the commemoration of religious holidays, and religion-based extracurricular activities. The habituation of these activities is carried out consistently, involving all members of the school community. The results of the study indicate that the habituation of religious activities contributes positively to the formation of students' religious character. Students showed improvements in worship discipline, responsibility, honesty, and mutual respect among the school community. Thus, the habituation of religious activities can serve as an effective strategy in internalizing religious character values at SMP Negeri Satap Gerokgak and can be used as a reference for other schools in developing religious character education.